Small Extracellular Vesicles Derived From MSCs Have Immunomodulatory Effects to Enhance Delivery of ASO-210 for Psoriasis Treatment - Zhang, Weixian; Lin, Jingxiong; Shi, Peilin; Su, Dandan; Cheng, Xiaoli; Yi, Wenkai; Yan, Jian; Chen, Hongbo; Cheng, Fang (Frontiers in Cell and Developmental Biology, 2022)
Mesenchymal stem cells (MSCs) have been increasingly used for treating autoimmune diseases due to their immune modulation functions, but inefficient homing to the target tissue and safety issues limit their widely application. Recently, increasing studies demonstrate small extracellular vesicles (sEVs) as key mediators of MSCs to exert their immune-modulatory effects. In this study, we found that sEVs derived from human umbilical cord MSCs stimulated by IFN-γ (IFNγ-sEVs) inhibited proliferation and activation of peripheral blood mononuclear cells and T cells in vitro. Furthermore, we confirmed that IFNγ-sEVs reduced psoriasis symptoms including thickness, erythema and scales of skin lesions, exhausted Th17 cells, increased Th2 cells and reduced enrichment of inflammatory cytokines such as IL-17A, IFN-γ, IL-6, TNF-α in both spleen and skin lesions in vivo. Importantly, IFNγ-sEVs significantly improved the delivery efficiency and stability of ASO-210, the antisense oligonucleotides of miR-210 to block the immune imbalance and subsequent psoriasis development. Our results reveal MSC-sEVs as promising cell-free therapeutic agents and ideal delivery vehicles of antisense oligonucleotides for psoriasis treatment.